Positron Emission Tomography to Improve Assessment of Interstitial Lung Disease in Patients With Systemic Sclerosis Eligible for Autologous Stem Cell Transplantation - Broens, Bo; van der Laken, Conny J.; Zwezerijnen, Gerben J.C.; Nossent, Esther J.; Meijboom, Lilian J.; Spierings, Julia; de Vries-Bouwstra, Jeska K.; van Laar, Jacob M.; Voskuyl, Alexandre E. (Frontiers in Immunology, 2022)
Positron emission tomography (PET) is a promising technique to improve the assessment of systemic sclerosis associated interstitial lung disease (SSc-ILD). This technique could be of particular value in patients with severe diffuse cutaneous SSc (dcSSc) that are possibly eligible for autologous hematopoietic stem cell transplantation (aHSCT). aHSCT is a potentially effective therapy for patients with severe dcSSc and ILD, leading to stabilization or improvement of lung function. However, there is a high need to improve patient selection, which includes (1) the selection of patients with rapidly progressive ILD for early rather than last-resort aHSCT (2) the prediction of treatment response on ILD and (3) the understanding of the mechanism(s) of action of aHSCT in the lungs. As previous studies with 18F-FDG PET in SSc-ILD and other forms of ILD have demonstrated its potential value in predicting disease progression and reactivity to anti-inflammatory treatment, we discuss the potential benefit of using this technique in patients with early severe dcSSc and ILD in the context of aHSCT. In addition we discuss the potential value of other PET tracers in the assessment of ILD and understanding the mechanisms of action of aHSCT in the lung. Finally, we provide several suggestions for future research.